Clinicopathological characteristics and management of patients with early readmission to our surgical oncology clinic - Çaparlar, Mehmet Ali; Dokcu, Şeref; Demirci, Salim (The European Research Journal, 2022)
Objectives: This study aimed to discuss the frequency of early readmission to the hospital after discharge in our oncology clinic, clinicopathological features, and management of these patients in light of current literature. Methods: The medical records of 237 early readmitted patients within 30 days of discharge in our clinic were retrospectively reviewed. The patients were categorized according to their first diagnosis, Eastern Cooperative Oncology Group (ECOG) performance status, demographic, clinicopathological characteristics, readmission reasons, first treatment type, postoperative complications, the time of application after discharge and the type of treatment after admission.Results: The mean age of the patients was 58.45 years, 57.4% were female, and the mean readmission time after discharge was 11.54 days. The most common primary diagnosis was gastric cancer (35.9%), and the most common emergency pathology requiring hospitalization was ileus-subileus (45.1%). After readmission, 42.6% of the patients received medical treatment. 60% of the readmitted patients had postoperative complications before discharge. Patients who had postoperative complications during the first hospitalization were more likely to have major or minor interventions after readmission (p < 0.01). Admission with a diagnosis of bowel obstruction was associated with the probability of major intervention (p < 0.01). Patients with an ECOG performance score of ≥2 was more frequently administered medical treatment (p = 0.001). Patients admitted with the diagnosis of anastomotic leak/abscess had a higher probability of having postoperative complications (p = 0.001). Conclusions: Readmissions are a concern for all healthcare providers, including comprehensive cancer centers. Recent health policies strive to reduce preventable admissions. Hence, we believe focusing on postoperative complications, and palliative care services is necessary.